Bipolar Disorder: A Major Setback in Substance Abuse (Indian Journal of Forensic Medicine & Toxicology, 2020)
Substance abuse refers to harmful or precarious use of psychoactive substances, including alcohol, cannabisand illicit drugs. It is directly and indirectly responsible for millions of morbidities each year. It is acrucial snag of present generation. Illegitimate use of psychoactive drugs can lead to lunatic illnesses. Theprevalence of psychotic disorders among patients with substance abuse has attended noticeable magnitude.This study indicates that bipolar disorder is more likely to occur in patients with substance abuse. Chronicsubstance abuse can lead to down-regulation of concerned receptors as well as erosion of gray matter in theprefrontal cortex of brain. Hence, it would be imperative to address bipolar disorder from the perspective ofpotential and progressive adverse effect of substance abuse. The observation of study indicates that bipolardisorder is more prevalent in cannabis, alcohol and cocaine abuse cases. Drug abuse disorders are associatedwith impaired outcome of manic depression maladies that brings severe high or low moods, thinking andbehavior.